Original articleAngiocentric glioma: a rare intractable epilepsy-related tumour in children - Grajkowska, Wiesława; Matyja, Ewa; Daszkiewicz, Paweł; Roszkowski, Marcin; Peregud-Pogorzelski, Jarosław; Jurkiewicz, Elżbieta (Folia Neuropathologica, 2014)
Angiocentric glioma is a low-grade tumour that occurs in children and young adults with a long-standing epilepsy. The typical histopathological features of this tumour is the presence of spindle-shaped cells, radially oriented around the cortical blood vessels. We present two teenage cases of the angiocentric variant of glioma: 1) a 15-year-old girl with a chronic and intractable partial epilepsy with cystic tumour located in the right temporal lobe and 2) a 14-year-old boy with intractable seizures and an extensive cortical lesion in the left parieto-occipital area. In both cases, the total tumours excision was performed. The histopathological findings revealed a characteristic angiocentric pattern that was composed of elongated cells arranging in pseudorosette-like structures around blood vessels. Moreover, schwannoma-like areas and subpial neoplastic infiltration with palisading of tumour cells at the brain surface were seen. The neoplastic cells displayed immunoreactivity for GFAP, S-100 protein and vimentin. A slight “dot-like” EMA staining, suggesting ependymal differentiation, was detected. The clinical and pathological picture allowed to establish the diagnosis of angiocentric gliomas. The patients were discharged home in a good condition and without seizures. During the 4-year follow-up, the tumour recurrence and seizures were not observed. The appropriate diagnosis of this peculiar type of usually low-grade glial tumour is important for adequate and successful treatment. The differential diagnosis requires the exclusion of other tumours with an angiocentric pattern, i.e. ependymoma, astroblastoma, which are associated with more aggressive biology.